Evaluation of Bacterial Contamination in Dressed Chickens in Lusaka Abattoirs - Mpundu, Prudence; Mbewe, Allan Rabson; Muma, John Bwalya; Zgambo, Jessy; Munyeme, Musso (Frontiers in Public Health, 2019)
Objective: Despite the rapid growth and intensification of poultry farming in Zambia, the processing has remained largely unhygienic. The presence of high levels of pathogenic bacterial contamination, such as Escherichia coli and salmonella among others pose serious public health concerns and production problems linked to shelf life. Accordingly, this study was formulated to evaluate bacterial contamination and risk factors linked to contamination of chickens during processing. Methods: The design was cross sectional across two main poultry abattoirs in Lusaka. The processing line was used to collect biological samples alongside risk-associated data questionnaire. Results: Eight (80) dressed chickens were sampled and out of these 56(70% 95% CI 58.9-79.2) were found to be contaminated. On specific bacteria enumeration, Salmonella alone only accounted for (0.025% 95% CI 6.1-9.7), while E.coli was (55% 95% CI 43.8-65.7). A statistically, significant difference (p <0.025) chi2 9.3874 was found between Total Coliform Counts and Escherichia coli. Both Total Coliform Counts and Escherichia coli levels were recovered in high numbers after carcass wash. Comparatively, pre-washing of chickens at post evisceration, 15(34.9%) were found to be contaminated, whilst 28(65.1%) of the carcasses were found to be contaminated at post washing. In addition, the number of processed chickens per day was also found to be statistically significant even after adjusting for other variables (AOR 4.5 95% CI 1.7-11.7) at p<0.002. Conclusion: Higher levels of bacterial contamination after washing the carcasses are likely to point to be due to using re-used water when processing. This is of serious concern from public health point of view. Furthermore, the presence of microbial indicator organisms in high numbers, such as Total Coliform Counts, Escherichia coli and Salmonella indicates unhygienic practices with little or no quality control systems being implemented. Significance: The most significant aspect that this study has bought out is the need to test water sources and the water used for processing given the high levels of microbial indicator organisms for contamination isolated under this study. Therefore there is need for policy makers to uptake such findings to guide policy in relation to hygienic practices at abattoirs to ensure and assure food safety.